PENGARUH STRUKTUR MODAL, KONEKSI POLITIK, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2023 - Dwi Anita, Amelia; Saraswati, Wiwik; Yuni Kartika, Ita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This study aims to examine the effect of Capital Structure, Political Connections, and Company Size on Company Value. The data used are the annual financial reports of non-financial companies listed on the Indonesia Stock Exchange (IDX) for the period 2023. The type of research used is quantitative research. The sampling technique uses a purposive sampling method which produces 717 company samples from a population of 832 companies. The data analysis method used is descriptive statistical analysis and multiple linear regression analysis. The test tools used are the classical assumption test, the coefficient of determination test (R2), and the t-test. The results of this study indicate that Capital Structure has no significant and negative effect on company value. The results of the Political Connection study have no significant effect on company value. The results of the Company Size study have a significant effect on company value